2006
DOI: 10.15517/rbt.v56i3.5710
|View full text |Cite
|
Sign up to set email alerts
|

Flesh flies species (Diptera: Sarcophagidae) from a grassland and a woodland in a Nature Reserve of Buenos Aires, Argentina

Abstract: Temporal changes of flesh flies abundance were simultaneously recorded at monthly intervals during a year in a woodland and in a grassland at the "Reserva Ecológica Costanera Sur" (RECS), Buenos Aires city, Argentina. Samples were taken at monthly intervals (February 2004-January 2005). Hourly captures of adult flies (10:00 am-04:00 pm) were taken each sampling date with a hand net. Temperature was recorded at each hourly capture. The baits used were 200 g of rotten cow liver and 200 g of fresh dog faeces. Rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
11
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 10 publications
4
11
0
1
Order By: Relevance
“…The high diversity associated with low abundance of Sarcophagidae observed in the rainforest fragment of Dois Irmaos State Park has also been found in other field studies (Mulieri et al 2008). The other dominant families among the emerged adults, Muscidae and Phoridae, are also commonly reported in larval stages in field experiments on forensic entomology (Segura et al 2011).…”
Section: Discussionsupporting
confidence: 81%
“…The high diversity associated with low abundance of Sarcophagidae observed in the rainforest fragment of Dois Irmaos State Park has also been found in other field studies (Mulieri et al 2008). The other dominant families among the emerged adults, Muscidae and Phoridae, are also commonly reported in larval stages in field experiments on forensic entomology (Segura et al 2011).…”
Section: Discussionsupporting
confidence: 81%
“…material 1). This species was also dominant in similar studies in a natural reserve in Buenos Aires, Argentina, where it was found associated with feces (Mariluis et al 2007, Mulieri et al 2008. In Brazil, it was the most abundant species in cow's lung tissue (Pereira de Sousa et al 2015) and the second most abundant in pig carcasses (Barbosa et al 2009), in buffalo excrements (Marchiori 2014), and the third most abundant in feces in the Archipelago Fernando de Noronha (Couri et al 2008).…”
Section: Discussionmentioning
confidence: 61%
“…Nephochaetopteryx cyaneiventris had been previously recorded from the states of São Paulo, Rio de Janeiro, and Paraná in Brazil (Lopes 1936;Mello-Patiu et al 2009;Vairo et al 2011), and from Argentina (Mulieri et al 2008(Mulieri et al , 2010. Vairo et al (2011) registered it for the first time on pig carcass after conducting a forensic experiment in the state of Paraná.…”
Section: Sarcophaga (Neobellieria) Polistensismentioning
confidence: 97%
“…Our record of N. cyaneiventris is therefore the second one in pig carcass, the species being more abundant in the forest site. In Buenos Aires, Argentina, this species was collected only in forest, attracted by rotten cow liver and feces (Mulieri et al 2008(Mulieri et al , 2010.…”
Section: Sarcophaga (Neobellieria) Polistensismentioning
confidence: 99%